اتجاهات التلاميذ نحو استخدام منصة الامتحانات DzExams في تحقيق العملية التعليمية دراسة ميدانية على عينة من تلاميذ السنة الرابعة متوسط بإكمالية - بوجلال حدة أولاد عدي لقبالة - - حموش سامي (جامعة محمد بوضياف بالمسيلة, 2025)
هدفت هذه الدراسة إلى بيان اتجاهات التلاميذ نحو استخدام منصة الامتحانات DZ Exams في تحقيق العملية التعليمية من خلال دراسة ميدانية على عينة من تلاميذ الرابعة متوسط بإكمالية بوجلال حدة بأولاد عدي لقبالة في ولاية المسيلة، حيث تم الاعتماد على المنهج الوصفي وأداة الاستبيان لجمع بيانات الدراسة على عينة متكونة من 40 تلميذ، وقد توصلت الدراسة إلى عدة نتائج منها: عادات وأنماط استخدام منصة الامتحاناتDZ Exams تختلف لدى تلاميذ الرابعة متوسط بإكمالية بوجلال حدة بأولاد عدي لقبالة في ولاية المسيلة في تحقيق العملية التعليمية على حسب الظروف التعليمة، وأن دوافع استخدم التلاميذ محل الراسة للمنصة تؤدي إلى تحسين العملية التعليمية، بالإضافة إلى أنه كلما كان زيادة في الإشباعات المحققة لاستخدام تلاميذ الرابعة بالمتوسطة لمنصة DZ Exams متعلقة بتحقيق العملية التعليمية أدى ذلك إلى زاد الناجح في الدراسة. This study aimed to demonstrate students' attitudes towards using the DZ Exams platform to achieve the educational process through a field study on a sample of fourth-year middle school students at Boujlal Hadda Secondary School in Ouled Addi Lakbala in the state of M'sila. The descriptive approach and questionnaire tool were used to collect study data on a sample of 40 students. The study reached several results, including: Habits and patterns of using the DZ Exams platform differ among fourth-year middle school students at Boujlal Hadda Secondary School in Ouled Addi Lakbala in the state of M'sila in achieving the educational process according to the educational circumstances, and that the motives for the students' use of the platform lead to improving the educational process, in addition to the fact that the greater the satisfaction achieved by fourth-year middle school students' use of the DZ Exams platform related to achieving the educational process, the more successful they are in the study.